Peningkatan Edukasi Dan Deklarasi Anti Bulliying Terhadap Siswa Siswa Sekolah Dasar Di Kota Tangerang Selatan - anggara satria pamungkas (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
This research aims to explore and evaluate the effectiveness of increasing education and anti-bullying declarations for elementary school students in South Tangerang City. The method used involves implementing a special educational program accompanied by an anti-bullying declaration in the school environment. The research results showed an increase in students' understanding of the negative impacts of bullying and a decrease in bullying incidents. This improvement is measured through participatory evaluation and analysis of pre- and post-program implementation survey data. These findings support the urgency of implementing similar programs in elementary schools to create a safe and supportive learning environment. This research provides valuable insight into the role of education and anti-bullying declarations in protecting students from bullying practices.